2016
DOI: 10.1016/j.jid.2016.06.617
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an S100A8 Receptor Neuroplastin-β and its Heterodimer Formation with EMMPRIN

Abstract: We previously reported a positive feedback loop between S100A8/A9 and proinflammatory cytokines mediated by extracellular matrix metalloproteinase inducer, an S100A9 receptor. Here, we identify neuroplastin-β as an unreported S100A8 receptor. Neuroplastin-β and extracellular matrix metalloproteinase inducer form homodimers and a heterodimer, and they are co-localized on the surface of cultured normal human keratinocytes. Knockdown of both receptors suppressed cell proliferation and proinflammatory cytokine ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…Besides classical S100A8/A9 receptors, toll-like receptor 4 (TLR4) 4,5 and receptor for advanced glycation end products (RAGE), 5,6 we have reported the presence of the important novel receptors including extracellular matrix metalloproteinase inducer (EMMPRIN), neuroplastin (NPTN)α and β, melanoma cell adhesion molecule (MCAM) and activated leukocyte cell adhesion molecule (ALCAM). [7][8][9][10][11][12] Among these receptors, we found that lung cancer cell lines highly express NPTNβ compared with normal cells lines ( Figure S1A). This finding was supported by the result of immunohistochemistry showing that NPTNβ was highly positive in lung cancer cells and that S100A8/A9 appeared in either cancer cells or the surrounding stroma in clinical specimens, suggesting that extracellular S100A8/A9 physiologically acts on cell surface NPTNβ in cancer cells in an autocrine manner as well as a paracrine manner ( Figure 1).…”
Section: Nptn and S100a8/a9 Are Highly Expressed In Lung Cancermentioning
confidence: 99%
“…Besides classical S100A8/A9 receptors, toll-like receptor 4 (TLR4) 4,5 and receptor for advanced glycation end products (RAGE), 5,6 we have reported the presence of the important novel receptors including extracellular matrix metalloproteinase inducer (EMMPRIN), neuroplastin (NPTN)α and β, melanoma cell adhesion molecule (MCAM) and activated leukocyte cell adhesion molecule (ALCAM). [7][8][9][10][11][12] Among these receptors, we found that lung cancer cell lines highly express NPTNβ compared with normal cells lines ( Figure S1A). This finding was supported by the result of immunohistochemistry showing that NPTNβ was highly positive in lung cancer cells and that S100A8/A9 appeared in either cancer cells or the surrounding stroma in clinical specimens, suggesting that extracellular S100A8/A9 physiologically acts on cell surface NPTNβ in cancer cells in an autocrine manner as well as a paracrine manner ( Figure 1).…”
Section: Nptn and S100a8/a9 Are Highly Expressed In Lung Cancermentioning
confidence: 99%
“…1 After publication of the report by Hiratsuka et al, the RAGE was also included as a soil sensor for S100A8/A9. 2 We then found further evidence of other important novel soil sensors for S100A8/A9: EMMPRIN, 3 NPTNβ, 4 MCAM and ALCAM. 5,6 We named the proteins "S100 soil sensor receptors, abbreviated as SSSRs."…”
Section: Introductionmentioning
confidence: 65%
“…After publication of the report by Hiratsuka et al ., the RAGE was also included as a soil sensor for S100A8/A9 . We then found further evidence of other important novel soil sensors for S100A8/A9: EMMPRIN, NPTNβ, MCAM and ALCAM . We named the proteins “S100 soil sensor receptors, abbreviated as SSSRs.” The relationship between S100A8/A9 and these receptors may be applicable to broad cancer species since S100A8/A9 is also utilized by breast cancer cells for lung tropic metastasis .…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations